Pengaruh Peer Pressure Terhadap Stress Akademik Pada Mahasiswa UIN Walisongo Semarang - Indy Rahma F; Ladya Ghaisani K; Dewi Khurun Aini (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Academic stress has become a worrying problem. Because this academic stress affects the performance in the classroom learning process of students. It is suspected that peer pressure is the cause of academic stress. This study aims to examine the influence of peer pressure on academic stress among students of UIN Walisongo Semarang. Using a survey method with a quantitative approach, data were collected from 200 students through a questionnaire that measured the level of peer pressure and academic stress. The results of statistical analysis using simple linear regression showed that there was no significant influence between peer pressure and academic stress, with a p-value greater than 0.05. This finding suggests that peer pressure is not the main factor influencing academic stress in students of UIN Walisongo Semarang. Discussion of the results of this study reveals that there may be other factors that are more dominant in determining the level of academic stress.